The claim of language : a case for the humanities - Fynsk, Christopher, 1952- (University of Minnesota Press, 2004)
In The Claim of Language, Christopher Fynsk clearly and eloquently defends and rearticulates the humanities from a perspective that moves beyond the political and philosophical reductions of identity politics. Leaving aside polemics, Fynsk asserts that discourses in the humanities will find real ethical-political purchase when they engage with the material events in art, literature, and social life that call for humanistic reflection.